Climatic suitability for Coffea arabica L. front to climate events extreme: Tree cover importance - Parada-Molina, Paulo César (2022)
Negative impacts of climate change are expected in the production of Coffea arabica L. one of the most commercialized tropical agroproducts in the world. However, most studies work with global circulation models, being of little use in making decisions on the scale of farm management. Given this, the objective of this study was to identify the suitability for the cultivation of C. arabica in the face of climate change and how tree cover mitigates the impacts of climate change in an agroforestry plot. The indices of climatic extremes were calculated (1961 to 2016 for Coatepec; 1985 to 2016 for Briones) and a trend analysis was carried out (Mann-Kendall). The temperature inside a plot, and on an open site, was monitored for two years (2017-2019). This was related to the climatic requirements of C. Arabica. Trends of increase (p < 0.05) of the minimum and minimum extreme annual temperatures were identified in the two stations near the plot (0.24 and 0.69 °C·decade-1 in Coatepec and 0.46 and 0.79 °C·decade-1 in Briones). The maximum temperature did not present significant increases, reducing the thermal amplitude. Both annual and seasonal precipitation shows trends of increase in intensity. All these conditions are still suitable for the cultivation of C. arabica. At the plot scale, the importance of tree cover is demonstrated, which in this agroforestry system allows to reduce the maximum temperature by 1.9 °C compared to an open site. Tree cover has also made it possible to mitigate extreme events.